2018
DOI: 10.1002/smll.201703617
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Multiplexed Drug‐Combination Screening Platforms Using 3D Microtumor Model for Precision Medicine

Abstract: Cancer heterogeneity is a notorious hallmark of this disease, and it is desirable to tailor effective treatments for each individual patient. Drug combinations have been widely accepted in cancer treatment for better therapeutic efficacy as compared to a single compound. However, experimental complexity and cost grow exponentially with more target compounds under investigation. The primary challenge remains to efficiently perform a large‐scale drug combination screening using a small number of patient primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…A logarithmic concentration gradient producer was proposed, providing a wider dynamic concentration range rather than a linear gradient producer. [78] Akay et al reported the use of a brain cancer chip to release two clinical drugs in the treatment of glioblastoma. The concentration gradient generated by the multiple microfluidic channels in the chip allowed the delivery of anticancer drugs at different concentrations.…”
Section: Drug Screening Devicesmentioning
confidence: 99%
“…A logarithmic concentration gradient producer was proposed, providing a wider dynamic concentration range rather than a linear gradient producer. [78] Akay et al reported the use of a brain cancer chip to release two clinical drugs in the treatment of glioblastoma. The concentration gradient generated by the multiple microfluidic channels in the chip allowed the delivery of anticancer drugs at different concentrations.…”
Section: Drug Screening Devicesmentioning
confidence: 99%
“…Most drug screening approaches generally rely on large-scale studies in populations with heterogeneity in individual patient differences. [4][5][6] However, this approach is still not ideal, because the results are obtained based on bulk analysis of a large number of cells, which neglects cellular heterogeneity within a patient, leading to the masking of specic cell information. To solve this problem, several single-cell drug screening systems for the analysis of cancer cell lines were established.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, traditional cell culture methods such as surface modification (Cui et al, 2019; Fukuda & Nakazawa, 2011), spinner flask (Friedrich, Ebner, & Kunz‐Schughart, 2007), microfluidic (Jin, Cho, Gu, Kim, & Oh, 2011; Liu et al, 2016; Zhang et al, 2018), handing drop (Antunes et al, 2019; Kwak, Lee, Lee, Lee, & Lim, 2018; Liu, Sun et al, 2019; Zhao et al, 2017), and liquid marbles (Vadivelu, Kamble, Munaz, & Nguyen, 2017; Vadivelu et al, 2015) have been widely applied to generate 3D tumors. However, each method has advantages and limitations (Breslin & O'Driscoll, 2013).…”
Section: Introductionmentioning
confidence: 99%